Increasing the Equilibrium Yield of Oxidative Dehydrogenation with CO2 by Secondary Reactions - Müller, Karsten; Baumgärtner, Andrea; Mokrushina, Liudmila; Arlt, Wolfgang (Chemical Engineering & Technology, 2014)
Oxidative dehydrogenation with carbon dioxide as an oxidant at low temperatures is strongly limited by its thermodynamic equilibrium. It is be shown that the equilibrium yield of the desired olefin can significantly be increased utilizing side reactions. This does not necessarily require the addition of another reactant, since this reactant can be formed in situ from the starting alkane. This effect allows for a decrease of the reaction temperature as well as the overall heat demand of the reaction. As a consequence, the exergy demand of the reaction system is reduced substantially.
Keywords: Carbon dioxide; Olefin; Oxidative dehydrogenation; Thermodynamic equilibrium

Potential analysis for the improvement of chemical energy transformation processes - Adametz, Patrick; Baumgärtner, Andrea; Kohler, Tobias; Obermeier, Jonas; Siebert, Daniel; Müller, Karsten (Chemical Engineering & Technology, 2017)
Much research aims to improve the efficiency of energy processes. However, it is often not clear where the biggest potential for improvement lies. Crucial for a namable improvement is a realistic chance for advancing the respective element as well as a significant influence of the respective element on the overall performance. A study on the potential for improving the efficiency of five exemplary chemical-energy systems is presented. It was found that replacing working substances by alternatives with better enthalpies of reactions or solubility behavior carries huge potential for improving energy processes. However, in most cases there is little potential, for example, in lower heat capacity, even though heat capacity highly influences the efficiency of the processes.